Buying brands at both regular price and on promotion over time. Issue 4 (November 2017) - Scriven, John; Clemente, Maria; Dawes, John; Trinh, Giang; Sharp, Byron
Highlights: The study examines brand purchasing by the same buyers both on and off price promotion in 16 consumer goods categories. The incidence of buying a brand only on promotion in a year is very strongly correlated with the overall extent of promotion occasions for that brand. The extent of apparent 'deal-proneness' in a category is therefore largely a function of the amount of promotions prevalent in a category. A brand's normal-price buyers are a major source of its volume from price promotions. Brand loyalty is shown to be still an important aspect of purchase, even in categories with very high levels of price promotion. Abstract: We analyse the purchasing of brands at both regular and promotional price over time. The goal is to better understand the extent of consumer deal-proneness. Our analysis shows most consumers buy brands on promotion at least some of the time, and the tendency to buy on promotion relates mostly to how much promotion is available in a category, suggesting little innate deal-proneness. The extent of promotion can be so high that as many as half of all brand buyers buy the brand solely when it is on promotion. However, this amount of on-deal buying is only very slightly higher than would be expected given the amount of promotion available. We find few buyers buy only on promotion. Promotion buyers of a particular brand also buy other brands on and off promotion more or less in line with the market share those other brands have at regular and promotional price. The three main implications are: (1) brand loyalty is still an important aspect of purchase, (2) a brand's normal-price buyers are a major source of its volume from price promotions, and (3) there is only a small effect of deal-proneness on promotion buying over and above that of promotion prevalence in a category. Chinese Abstract: 我们分析了在很长一段时间内，消费者购买常规和促销价格品牌商品的情况。目标是更好地了解消费者的促销倾向程度。我们的分析显示，大多数消费者至少在某些时候购买促销的品牌，并且购买促销品的倾向主要与某个类别的商品中提供了多少促销相关，表明没有什么天然的促销倾向。促销的作用如此之大，以至于所有品牌的消费者中，有一半是仅在该品牌做促销时才会购买的。然而，考虑到可用的促销数量，这种捡便宜式购买的数量仅比预期高出一点点。我们发现，只有极少数消费者会仅仅在促销时进行购物。某个品牌的促销买家也会或多或少购买其他品牌，随着其他品牌所占的市场份额，以常规价格和促销价格购买。三个主要结论是：（1）品牌忠诚度仍然是购买的一个重要方面，（2）品牌的正常价格买家是价格促销购买力的主要来源，（3）在同一类别中，消费者的促销倾向比起促销推广度，仅有微小的效果。